ali48
ali48
16-07-2017
Mathematics
contestada
F(x) =x^2+6x and g(x)=7-x find (f-g)(x) and (f-g)(9)
Respuesta :
Banabanana
Banabanana
16-07-2017
(f-g)(x) = x²+6x - (7-x)
(f-g)(x) = x² + 6x - 7 + x
(f-g)(x) = x² + 7x - 7
(f-g)(9) = 9² + 7*9 - 7
(f-g)(9) = 81 + 63 - 7
(f-g)(9) = 137
Answer Link
VER TODAS LAS RESPUESTAS ( 78+ )
Otras preguntas
Derived quantities depend on...........physical quantity
The telephone numbers in a small town have two digits. They run from 00 to 99. Of the 100 possible numbers, those that become smaller when reversed are not used
look at the image below
Which sentence is punctuated correctly?
Why might the unnamed first-person narrator be telling the story during the exposition in The Time Machine? A. Because the narrator is going to have a larger pa
look at the image for the question
Which affirmative word best completes the conversation? Carlos: Hola, Laura, dime ____ sobre los gauchos de Argentina. Laura: Bueno, ché, te cuento lo que sé. O
यात्रा सुरु गर्दा समय किन अनुकुल छ?
The volume of a cylinder varies jointly with the square of its radius and with its height: V=kr2h Cylinder A has a volume of 254.34 cubic inches and has a radiu
-p/3-8=3 what is the variable
ACCESS MORE